The EU carbon border adjustment mechanism between ambition and delusion - Gianmarco I. P. Ottaviano (EconPol Forum, 2023)
Climate change is a global problem that calls for, among other measures, global carbon taxation. As not all countries tax carbon, those with higher carbon taxes, such as the EU members, face the risk of "carbon leakage". The Carbon Border Adjustment Mechanism (CBAM) makes the carbon price of imports equivalent to that of EU domestic production, and creates incentives for its trade partners to tax carbon to improve access to the single market. It does little, however, to help EU firms compete in foreign markets with producers from countries that do not tax carbon. Moreover, as trade relations increasingly follow geopolitical fault lines, the EU might overestimate the incentives CBAM creates unless its coordination with the US improves.
Keywords: 330